The Evolving Doctrine of Primacy - Hietanen, Ari (My University, 2022)
Primacy of EU law is the fundamental principle of law on which full and uniform application of EU law, the rule of law among it, is based on. Primacy has no explicit statutory basis but is founded on the case law of the Court of Justice of the European Union. The principle states that in case Union law and national law are in an irresolvable conflict so that the two norms cannot be brought to conformity by interpretation, the national law, irrespective of its domestic hierarchical status, is to be disapplied in the particular case. In the last few years rule of law backsliding has taken place in several of the Member States and the constitutional bodies in those and some of the other Member States have declared statements that openly challenge primacy. Meanwhile the Court has given two judgments that appear to deviate from the established doctrine of primacy in that the national measure was to be annulled instead of merely disapplied due to primacy. Inspired by these developments, I study in the thesis what is the content of primacy on the basis of case law and legal literature and examine whether the recent rulings of the Court reflect a true change in primacy, and if so, why would that be the case. My research methods consist of legal dogmatics supplemented with legal, especially constitutional theory. I conclude that primacy has two aspects: It manifests itself as an absolute rule that demands application of EU law and as a much more relative principle defining the consequences of application of EU law. These consequences can vary from disapplication to annulment of the national measure depending on the situation and are guided by the requirements of fulfilling other general principles of EU law. Based on research findings, I propose that very little, if at all, room is left for determining the effects of primacy on the basis of national constitutional identity. Thus, primacy is closely related to the constitutional nature of the EU and the Court appears to have harnessed the principle as its arm in its defense against breaches of the rule of law in Member States.

Euroopan unionin oikeuden ensisijaisuus on perustavanlaatuinen oikeudellinen periaate, johon EU-oikeuden, oikeusvaltioperiaate mukaan luettuna, täysi ja yhdenmukainen soveltaminen perustuu. Etusijaperiaate ei ole lakiin kirjoitettu vaan se on muodostunut Euroopan unionin tuomioistuimen oikeuskäytännön pohjalta. Periaatteen mukaan, jos unionin oikeus on jossakin tapauksessa kansallisen oikeuden kanssa sellaisessa ratkaisemattomassa ristiriidassa, ettei näitä normeja voida tulkinnallisesti sovittaa yhteen, on kansallinen normi jätettävä soveltamatta riippumatta sen valtionsisäisestä oikeuslähdeasemasta. Viimeisten vuosien aikana oikeusvaltioperiaatteen toteutuminen on vaarantunut useissa jäsenvaltioissa ja näiden sekä joidenkin muidenkin jäsenvaltioiden perustuslailliset elimet ovat antaneet lausuntoja, jotka avoimesti kyseenalaistavat etusijaperiaatteen. Sillä välin EU-tuomioistuin on antanut kaksi tuomiota, jotka poikkeavat vakiintuneesta etusijaperiaatteen soveltamistavasta siinä, että kansallinen toimi oli periaatteen nojalla kumottava pelkän soveltamatta jättämisen sijaan. Näiden kehityskulkujen innoittamana selvitän tutkielmassa oikeuskäytäntöön ja oikeuskirjallisuuteen nojautuen mikä on EU-oikeuden etusijaperiaatteen sisältö ja tutkin, heijastavatko EU-tuomioistuimen viimeaikaiset tuomiot etusijaperiaatteen todellista muutosta ja miksi näin olisi. Tutkimusmenetelminäni hyödynnän lainoppia oikeusteorialla, ja erityisesti valtiosääntöteorialla, täydennettynä. Johtopäätöksenäni esitän etusijaperiaatteella olevan kaksi puolta: Se ilmenee yhtäältä ehdottomana sääntönä, joka edellyttää EU-oikeuden soveltamista, ja toisaalta paljon suhteellisempana periaatteena, joka määrittää EU-oikeuden soveltamisen seurauksia. Nuo seuraukset voivat tapauksesta riippuen olla kansallisen toimen soveltamatta jättäminen tai kumoaminen ja niiden valintaa ohjaa muiden EU-oikeuden yleisten periaatteiden toteutumisen edellytykset. Tutkimustulosteni perusteella esitän, että etusijaperiaatteen vaikutusten määräytymisessä kansalliselle valtiosääntöidentiteetille annetaan vain vähän, jos lainkaan, merkitystä. Siten etusijaperiaate liittyy läheisesti Euroopan unionin valtiosääntöiseen luonteeseen ja EU-tuomioistuin vaikuttaa valjastaneen periaatteen aseekseen sen puolustautuessa jäsenvaltioissa tapahtuvia oikeusvaltioperiaatteen rikkomuksia vastaan.
Keywords: primacy, direct effect, rule of law, national constitutional identity